Peran Guru dalam Menginternalisasi Penggunaan Adawat al-Istifham dan Dhama’ir dari Teks Percakapan - Kasmaluddin (Ukazh : Journal of Arabic Studies, 2025)
This study examines the role of teachers and pedagogical strategies in internalizing the use of Adawât al-Istifhâm (interrogative words) and Dhama’ir (pronouns) in Arabic conversation learning. Internalizing these communicative elements is crucial to addressing the gap between structural knowledge and speaking practice. This study uses a descriptive qualitative approach grounded in language acquisition theory (Krashen) and social constructivism (Vygotsky). Data were obtained through observation, semi-structured interviews, and documentation during intensive Daurah Ramadhaniyah activities. The results indicate that teachers have four main roles: Language Model, Facilitator (providing scaffolding), Evaluator (error analysis), and Motivator (lowering the affective filter). Effective strategies include chained questioning (as-su’āl al-mutatabi‘), role simulations, and repeated text readings. The novelty of this study lies in the synthesis of these teacher roles within a scaffolding framework for intensive learning contexts. The implication is that successful internalization requires a balance between providing adequate input and affective support that fosters spontaneous speaking habits, characterized by the appropriate use of adawât and dhama’ir.